Intolerance of uncertainty as a vulnerability factor for excessive and inflexible avoidance behavior. - Flores, Amanda; López-Gutiérrez, Francisco José; Vervliet, Bram; Cobos-Cano, Pedro Luis (Elsevier, 2018)
Recent studies have shown that avoidance behavior may become excessive and inflexible (i.e., detached from its incentive value and resistant to extinction). On the other hand, prospective intolerance of uncertainty (P-IU) has been defined as a factor leading to excessive responding in uncertain situations. Thus, uncertain avoidance situations may be taken as a relevant scenario to examine the role of intolerance of uncertainty as a factor that facilitates excessive and inflexible avoidance behavior. In our experiment, we tested the hypothesis that P-IU is associated with excessive and inflexible avoidance in an outcome devaluation paradigm. Specifically, healthy participants learned in a free-operant discriminative task to avoid an aversive sound, and were tested in extinction to measure the sensitivity of avoidance responses to the devaluation of the sound aversiveness. The results showed that an increase in P-IU was positively associated to an increase in insensitivity to the devaluation. Moreover, P-IU was also related to an increase in the frequency of avoidance responses during the instrumental learning phase, and to resistance to extinction. Interestingly, these associations involving P-IU were still significant when trait anxiety was controlled for. The pattern of results suggests that P-IU may be a vulnerability factor for excessive and inflexible avoidance, which, in turn, has been found to be associated with several mental disorders.
Política de acceso abierto tomada de: https://openpolicyfinder.jisc.ac.uk/id/publication/16735
Keywords: Evitación (Psicología); Avoidance; Intolerance of uncertainty; Outcome devaluation; Generalization of avoidance behavior